Alkaloids and Flavones from Desmos dumosus, Roxb. Salt. (Annonaceae) - Sulaiman, Mazdida; A. Hadi, A. Hamid; Awang, Khalijah (Malaysian Journal of Science, 2003)
Eleven isoquinoline alkaloids and two flavones were isolated from the leaves and stem-barks of $Desmos$ $dumosus$. The alkaloids identified were $o$-methylmoschatoline, lysicamine, $O$-methylisopiline, discretamine, stepharine, pronuciferine, asimilobine, norlirioferine, nornuciferine, 3-hydroxynornuciferine and liriodenine. The two flavones isolated were 5-hydroxy-6,7-dimethoxyflavone and 5-hydroxy-7,8-dimethoxyflavone. The structures were determined by the usual spectroscopic technique.